Precise Control of Phase Separation Enables 12% Efficiency in All Small Molecule Solar Cells. Issue 34 (2nd August 2020) - Bin, Haijun; Angunawela, Indunil; Qiu, Beibei; Colberts, Fallon J. M.; Li, Mengmeng; Dyson, Matthew J.; Wienk, Martijn M.; Ade, Harald; Li, Yongfang; Janssen, René A. J.
Abstract: Compared to conjugated polymers, small‐molecule organic semiconductors present negligible batch‐to‐batch variations, but presently provide comparatively low power conversion efficiencies (PCEs) in small‐molecular organic solar cells (SM‐OSCs), mainly due to suboptimal nanomorphology. Achieving precise control of the nanomorphology remains challenging. Here, two new small‐molecular donors H13 and H14, created by fluorine and chlorine substitution of the original donor molecule H11, are presented that exhibit a similar or higher degree of crystallinity/aggregation and improved open‐circuit voltage with IDIC‐4F as acceptor. Due to kinetic and thermodynamic reasons, H13 ‐based blend films possess relatively unfavorable molecular packing and morphology. In contrast, annealed H14 ‐based blends exhibit favorable characteristics, i.e., the highest degree of aggregation with the smallest paracrystalline π–π distortions and a nanomorphology with relatively pure domains, all of which enable generating and collecting charges more efficiently. As a result, blends with H13 give a similar PCE (10.3%) as those made with H11 (10.4%), while annealed H14 ‐based SM‐OSCs have a significantly higher PCE (12.1%). Presently this represents the highest efficiency for SM‐OSCs using IDIC‐4F as acceptor. The results demonstrate that precise control of phase separation can be achieved by fine‐tuning the molecular structure and film formation conditions, improving PCE and providing guidance for morphology design. Abstract : Three homologous small molecule donors with hydrogen, fluorine, and chlorine substitution afford organic solar cells with efficiencies over 10% in combination with a common acceptor. The chlorinated derivative exhibits a more crystalline nanomorphology with relatively pure domains and provides more than 12% efficiency.